PENGARUH GEOGRAPHY FOR KIDS SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN KETERAMPILAN GEOGRAFIS PESERTA DIDIK DI SEKOLAH DASAR - Dine Rizky Pratiwi, - (2019)
This research was conducted at the Elementary School level which studies the learning of Geography in the Social Sciences (IPS) family. The idea originated from low simple geographical skills among elementary school students. One possible reason is that geography is not taught as a whole subject because geography is included in the IPS integrated learning family. What will be examined in this research is the influence of Geografphy for Kids material to improve geographical skills. This research is a quasi-experimental study and was conducted at SDN Ciawi 1 and SDN Srogol 1 Bogor Regency with a total sample of 20 people. The independent variable is Geography for Kids which is divided into indicators namely Location, Place, Human Interaction with the Environment while the dependent variable is Geography Skills. Data analysis was performed using multiple linear regression with the help of SPSS 23 software. The results showed that Geography for Kids had an effect on improving geographical skills positively and significantly. All geographical skills indicators have improved. Location indicator occupy the highest rank. The lowest indicator is human interaction with the environment. Keyword : Geography for Kids, Geographic Skills.